Triarchic Model of Psychopathy: A Brief Measure Among Detained Female Youths. Issue 11 (2nd November 2018) - Pechorro, Pedro; Simões, Mário R.; Alberto, Isabel; Ray, James V.
ABSTRACT: The present study examined the psychometric properties of a brief measure of the Triarchic model of psychopathy based on the Youth Psychopathic Traits Inventory (YPI-Tri-S) among a forensic sample of detained female youth offenders ( M = 16.41 years; SD = 1.19 years) from Portugal. Results supported the expected three-factor structure and cross-gender measurement invariance. The YPI-Tri-S showed good psychometric properties in terms of factor structure, internal consistency, convergent validity, discriminant validity, and criterion-related validity. Findings suggest that the YPI-Tri-S is a valid and reliable measure of the Triarchic model of psychopathy, which can be used to assess female juvenile offenders.